Hubungan Kadar Timah Hitam (Pb) dengan Kadar Albumin dalam Darah dan Kejadian Anemia (Studi pada pekerja peleburan timah di perkampungan industri kecil (PIK) Kebasen Kab. Tegal) - Muchtar Mawardi; Onny Setiani; Suhartono Suhartono (Jurnal Kesehatan Lingkungan Indonesia, 2013)
Background: Exposure to lead (Pb) with low levels over a prolonged period will cause health effects such ashypertension, anemia, decreased ability to inhibit the formation of the brain and red blood. If this is not resolvedsoon, disorder may result in disruption to the body’s various organ systems such as the nervous system, kidneys,reproductive system, gastrointestinal tract and anemia.This research aimed to know the association between leadexposure with albumin level and anemia.Methods: Cross-sectional study on 45 subjects research at Small Industry Village (PIK) Kebasen Talang DistrictTegal regency. Pb levels in the blood as biomaker of exposure to decreased levels of albumin and anemia.Result: There were 6 subjects who had BLL over the threshold with mean and standart deviation of 26.8 + 18.85ug/dl.They (33 sub) also had a haemoglobine level over the threshold with the mean of 14.3 + 1.10 gr %. Therewere 31 subjects with level of albumine over the threshold with the mean of 5.7+ 1.39. There was a relationshipbetween blood lead level and albumin level (p value = 0.048), with a correlation coefficient (rho) = -0.205.Conclusion: People who are working with very risky Pb exposure increased levels of albumin in the blood.Key words: Lead exposure, level of Albumin and Hemoglobin.